Encounters by the Rivers of Babylon: Scholarly Conversations Between Jews, Iranians and Babylonians in Antiquity - Gabbay, Uri (Texts and Studies in Ancient Judaism, 2015)
Cover -- Table of Contents -- Uri Gabbay and Shai Secunda: Introduction -- Yaakov Elman: Contrasting Intellectual Trajectories: Iran and Israel in Mesopotamia -- I. Introduction -- Mesopotamia in Ancient Iranian and Jewish Cultures -- II. Listenwissenschaft and Its Lessons -- III. Analogy as a Legal Trope -- IV. Self-Referentiality in Avesta and Pentateuch -- V. Cosmopolitanism, Writing, and Listenwissenschaft -- VI. Sasanian Casuistics: Rabbis and Dastwars -- VII. The Turn to Conceptualism -- VIII. Zoroastrian Legal Midrash -- IX. The Problem of Indeterminacy -- X. Rabbinic and Zoroastrian Listenwissenschaft -- XI. The End of Late Antiquity -- Bibliography -- Society and Its Institutions -- Ran Zadok: Judeans in Babylonia - Updating the Dossier -- Appendix: Sample list of people with šarru-names belonging to the palatial sector -- Bibliography -- Caroline Waerzeggers: Locating Contact in the Babylonian Exile: Some Reflections on Tracing Judean-Babylonian Encounters in Cuneiform Texts -- Introduction: The Social Location of Exiled Peoples in Tanzania and Babylonia -- From Person to Text and Archive -- Pathways in Texts and Society -- The Case of the Chronicles -- Incidental or Structural? -- Conclusion -- Bibliography -- Maria Macuch: Jewish Jurisdiction within the Framework of the Sasanian Legal System -- Bibliography -- The Transmission of Knowledge -- Abraham Winitzer: Assyriology and Jewish Studies in Tel Aviv: Ezekiel among the Babylonian literati -- I. Introduction -- II. Babylon in Ezekiel: Introductory Matters -- III. Babylon in Ezekiel: An Echo of Babylonian Scholastics -- IV. Ancient Encounters with the Epic of Gilgamesh (EG) -- V. Babylon in Ezekiel: The Epic of Gilgamesh -- VI. The Epic of Gilgamesh in Ezekiel: Contextual Considerations (I) -- VII. The Epic of Gilgamesh in Ezekiel: Contextual Considerations (II).